Comparison of the Effectiveness of Lifestyle-Focused Cognitive Behavioral Therapy and Semantic Cognitive Restructuring Therapy on Pain Perception in Patients with Irritable Bowel Syndrome - Akbari Ebtekar, Mozhgan; Emadian , Seyedeh Olia; Mirzaian , Bahram (Health Nexus, 2024)
This study aimed to compare the effectiveness of lifestyle-focused cognitive behavioral therapy and semantic cognitive restructuring therapy on pain perception in patients with irritable bowel syndrome. This quasi-experimental study utilized a pretest-posttest-follow-up design with a control group. The statistical population included all patients with irritable bowel syndrome in Babol city in 2023, selected through convenience sampling and randomly assigned to two experimental groups and one control group. Data were collected using the Pain Perception Scale developed by Schallz et al. (2010). The lifestyle-focused cognitive behavioral therapy group received eight 90-minute sessions, while the semantic cognitive restructuring therapy group received twelve 90-minute sessions, both conducted once a week. The control group did not receive any intervention. Data analysis was performed using a mixed design with repeated measures and SPSS-26 software. The results indicated that both lifestyle-focused cognitive behavioral therapy and semantic cognitive restructuring therapy were effective in reducing pain perception in patients with irritable bowel syndrome (P < 0.05). Moreover, lifestyle-focused cognitive behavioral therapy had a higher impact on reducing pain perception compared to semantic cognitive restructuring therapy in patients with irritable bowel syndrome. The present study demonstrated that lifestyle-focused cognitive behavioral therapy and semantic cognitive restructuring therapy are effective in reducing pain perception in patients with irritable bowel syndrome. Therefore, these approaches can be utilized alongside medical interventions in treatment centers for such individuals.